The Impact of Continuous Labor Support on Cesarean Section Rates among Nulliparous Women: A Randomized Controlled Trial - Hermatuti, Hermatuti (Archives of The Medicine and Case Reports, 2024)
Cesarean section (CS) rates are increasing globally, raising concerns about maternal and neonatal morbidity. Continuous labor support (CLS) has been shown to reduce CS rates in some settings, but its impact in Indonesia remains understudied. This study aimed to evaluate the effect of CLS on CS rates among nulliparous women in Purwakarta Regency, Indonesia. A randomized controlled trial was conducted at the Purwakarta Regional Hospital from January 2022 to December 2023. Eligible nulliparous women in labor were randomized to receive either CLS (n=210) from a trained midwife or standard care (n=205). The primary outcome was the rate of CS. Secondary outcomes included duration of labor, use of analgesia, maternal satisfaction, and neonatal outcomes. The CS rate was significantly lower in the CLS group (18.1%) compared to the standard care group (29.3%) (p=0.02). Women in the CLS group also reported higher satisfaction with their birth experience. No significant differences were found in other secondary outcomes. Continuous labor support provided by a trained midwife significantly reduces CS rates among nulliparous women in Purwakarta Regency, Indonesia. Implementing CLS as a routine practice may help address the rising CS rates and improve maternal birth experiences in this setting.